Truth, and the little red light: Krog, A (1998) Country of my skull. Johannesburg: Random House ISBN 0-958-41951-5 pbk. viii + 286 pages - Hayes, Grahame (PINS-Psychology in Society, 2026)
Antjie Krog’s book on her "close encounters" with the TRC has received a lot of attention. I would guess that it still is the most talked about, and written about, text on the TRC. What is it in this text that has attracted so much interest and critical debate? Are some of the answers to this question located in the multiple identities of its author? Afrikaner; white woman; (radio) journalist; renowned poet Surely so, and yet it is the complex interaction of these identities that mark Krog’s reflections on the TRC.